A Pilot Randomized Controlled Trial of Smoking Cessation in an Outpatient Respirology Clinic - Smita Pakhale; Justine Baron; Michael A Armstrong; Avanti Garde; Robert D Reid; Gonzalo Alvarez; Debbie Aitken; Kerri-Anne Mullen; George Wells; Andrew Pipe (Canadian Respiratory Journal, 2015)
OBJECTIVE: To assess the feasibility and potential effectiveness of a modified version of the Ottawa Model for Smoking Cessation in an outpatient respirology clinic.